Diabetic myonecrosis: a rare complication of poorly controlled diabetes - Indrakumar, Jegarajah; Udayakumaran, Perumal; Shangavi, Navaretnam; Direcksze, Naveen D. K. N. (International Journal of Research in Medical Sciences, 2025)
Diabetic myonecrosis is a rare complication of poorly controlled diabetes that can be overlooked. This case report describes a 58-year-old man with type 2 diabetes who presented with severe pain and swelling in his right anterolateral thigh for one month. Despite antibiotics, his symptoms persisted. Laboratory tests revealed a normal white blood cell count, elevated blood glucose levels, an elevated erythrocyte sedimentation rate, and elevated C-reactive protein levels. Magnetic resonance imaging revealed diffuse oedema in the anterior thigh muscles, strongly suggesting muscle necrosis. The patient was diagnosed with diabetic myonecrosis based on clinical presentation, basic investigations and imaging findings. He was managed with rest, pain control, and improved glycemic control. This case highlights the importance of considering diabetic myonecrosis in patients with poorly controlled diabetes who present with acute muscle pain and swelling. Early recognition and appropriate management are crucial for avoiding unnecessary interventions and improving outcomes. Increased awareness of this complication is needed among clinicians to ensure prompt diagnosis and treatment.